2019
DOI: 10.1017/s1463423619000859
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation and health literacy among young adults seeking care in Sweden: findings from a cross-sectional and retrospective study with questionnaire and registry-based data

Abstract: Aim: The objective of this study was to examine young adults’ healthcare utilisation and its possible association with health literacy. Background: Many countries struggle with insufficient accessibility at emergency departments (EDs) and primary healthcare centres (PHCs). Young adults, aged 20–29 years old, account for a substantial number of unnecessary doctor visits where health literacy could be an explanatory factor. Method: This study incorporated a combined retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Health literacy is also a factor when seeking healthcare in regards to approachability (i.e., comprehending information, identifying services, and participating in outreach activities) [ 34 ]. Earlier research has shown that patients with insufficient health literacy have lower reliance on healthcare systems [ 2 ]. If healthcare wants to change how young adults seek care, it is important to foster trust, reliance, and transparency [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Health literacy is also a factor when seeking healthcare in regards to approachability (i.e., comprehending information, identifying services, and participating in outreach activities) [ 34 ]. Earlier research has shown that patients with insufficient health literacy have lower reliance on healthcare systems [ 2 ]. If healthcare wants to change how young adults seek care, it is important to foster trust, reliance, and transparency [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The period for data collection was April 2017 to June 2018. As participants were recruited from an earlier study [ 2 ], the inclusion criteria followed the requirements of that study: age 20–29 years, speaking and understanding the Swedish language, and seeking care for a minor injury or disease at that particular healthcare visit. Thereafter, theoretical sampling was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many literatures have discussed about the significant effect that is being caused by the COVID-19 i.e., the limitations and the needs of improvement on infrastructure and utility [7,12,16], participation of community [6,17], and human movement by tracking and movement modelling [9,10,18]. But, during this pandemic, it is important to have information on how the condition of existing health care capacities, especially Referral Hospital for COVID-19 in Jakarta in contrast to the demand.…”
Section: Introductionmentioning
confidence: 99%